The distribution of HLA-DRB alleles in ulcerative colitis patients in Turkey - (:unkn) unknown (WILEY, 1998)
Recently described distinct associations of HLA class II genes with ulcerative colitis (UC) suggest a genetic heterogeneity for disease susceptibility. In this study, HLA-DRB alleles of UC patients (n = 59) from Turkey were investigated and compared with healthy controls (n = 244). Using molecular genotyping by polymerase chain reaction (PCR) and sequence-specific oligonucleotide hybridization, we have shown a positive association of UC patients with the HLA-DRB1*1502 allele (10/59 vs. 16/244; P = 0.02; OR: 2.9) and a negative association with the DRB1*13 allele (7/59 vs. 64/244; P = 0.03; OR: 0.38) compared to controls. HLA-DRB1*0701 was significantly increased in perinuclear antineutrophil cytoplasmic antibody (pANCA)-positive UC patients compared to pANCA-negative patients (8/32 vs. 0/27; P = 0.005), whereas DRB1*1502 was observed more frequently in pANCA-negative patients (8/27 vs. 2/32; P = 0.03). These results extended the reported positive association of DRB1*1502 with UC to another population and supported the genetic susceptibility associated with HLA genes for disease development.
Keywords: INFLAMMATORY BOWEL-DISEASE; ANTINEUTROPHIL CYTOPLASMIC ANTIBODIES; MAJOR HISTOCOMPATIBILITY COMPLEX; CLASS-II; CROHNS-DISEASE; GENES; SUSCEPTIBILITY; RISK